Determination of water content in infant formula - Jurković, Josip; Sulejmanović, Jasmina; Tahmaz, Jasmina; Gavrić, Teofil (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2019)
Water is one of the most important constituents of food, very important to be accurately quantified. Furthermore, water content affects the stability and shelf life of food. The evaluation of most chemical parameters is based on dry mass and many methods use heating which result in losing all volatile compounds, including water. Also, it is much harder to extract all of water if we have a complex matrix. Regarding this, the aim of this study was to determine water content in different infant formula by various methods. For examination of water content in three different types of infant formula three different techniques were used (oven sample processor, drying oven and halogen drying) and compared to classical Karl Fischer titration with two different solvents. Each sample was measured in ten probes, and classical Karl Fischer titration was used as a reference.  The results showed that the reference method was the best regarding speed of measurement, amount of sample needed and obtained water contents (3.01- 4.35%), followed by Karl Fischer in boiling methanol (2.80-4.30), oven sample processor (2.96-4.23%), halogen drying (2.74-4.03%) and drying oven (2.38-3.52). Methods using heating could not remove all water from the sample within a reasonable time.